Comparison of two algorithms of APTT-based lupus anticoagulant assay, two Dilute Russell viper venom time reagents, and silica clotting time - Preechaya Wongkrajang; Titiwan Pientong; Ratchaneekorn Hanyongyuth; Panutsaya Tientadakul (PLoS ONE, 2026)
Lupus anticoagulants (LA) are heterogeneous antiphospholipid antibodies that interfere with phospholipid-dependent coagulation assays, resulting in considerable variability among detection methods. Although international guidelines recommend a stepwise approach incorporating screening, mixing, and confirmatory testing, integrated strategies omitting routine mixing studies are widely used. Different percentile-based cutoffs have been proposed for defining LA positivity.We retrospectively analyzed 135 citrated plasma samples requested for LA testing. Five LA detection approaches were evaluated: 4 integrated assays and 1 activated partial thromboplastin time (APTT)–based approach following the ISTH-recommended stepwise algorithm with a mixing study. The integrated assays comprised silica clotting time, dilute Russell viper venom time (dRVVT) using 2 different reagent systems, and an APTT-based assay. Precision studies and reference intervals were established, and LA positivity rates were compared using 97.5th and 99th percentile cutoffs. Inter-assay agreement and associations with anticardiolipin (aCL) and anti–β2-glycoprotein I (aβ2GPI) antiphospholipid antibodies were assessed. LA positivity rates varied across procedures (19.3%–35.6%) at the 97.5th percentile. Application of the 99th percentile decreased positivity for dRVVT-HemosIL and APTT-based assays. Positivity increased at the 97.5th percentile in patients tested according to ISTH indications, with minimal impact in noncompliant cases. Inter-assay agreement ranged from fair to substantial and was influenced by assay type and cutoff definition. APTT-based assays showed the strongest associations with aCL and aβ2GPI antibodies. LA detection is strongly influenced by assay selection and cutoff strategy. Positivity rate–based evaluation provides a practical framework for comparing LA assays in laboratory practice, particularly in the absence of a reference standard.